Evaluasi Kualitas Estetika Lanskap Kawasan Ekowisata Cengkih Afo, Ternate, Maluku Utara - Rianate, Clara Arabella; Gunawan, Andi; Hadi, Akhmad Arifin (Jurnal Lanskap Indonesia, 2024)
“Cengkih Afo” is one of the original varieties of cloves from the city of Ternate. Currently, the Cengkih Afo area has been developed into a tourist destination that offers the beauty of nature, local culture and the Cengkih Afo Clove Tree itself. However, some areas within the region are not well-maintained, necessitating further evaluation of the aesthetic quality of the Cengkih Afo tourist area to enhance its existing tourism potential. The study aims to evaluate the aesthetic quality of the Cengkih Afo recreation area based on visitor perception. Method used in this research was the descriptive method by using the Scenic Beauty Estimation (SBE) and Semantic Differential (SD) analysis. The research results show the Cengkih Afo ecotourism area has very diverse aesthetic qualities as indicated by the SBE (Scenic Beauty Estimate) value, from the lowest value (SBE = -45) to the highest value (SBE = 113). High aesthetic quality shows that natural and artificial features are integrated harmoniously, neatly (orderly), and safe to move inside. The moderate aesthetic quality shows that the relationship between the two features is less harmonious and the forming elements are less neatly arranged. Low aesthetic quality indicates the presence of landscape elements that endanger visitors. Redesign is one of the important recommendations for improving the aesthetic quality of the ecotourism area.